Shifted fractional Jacobi spectral algorithm for solving distributed order time-fractional reaction–diffusion equations - Abdelkawy, M. A.; Lopes, António M.; Zaky, M. A. (Computational & applied mathematics, 2019)
This paper proposes a new method for solving distributed order time-fractional reaction–diffusion equations (DO-TFRDEs). Extended versions of the shifted Jacobi–Gauss–Lobatto and shifted fractional order Jacobi–Gauss–Radau collocation methods are developed for reducing the DO-TFRDEs to systems of algebraic equations and computing their approximate solutions. The applicability and accuracy of the method is illustrated through numerical examples.